1995
DOI: 10.2307/2950548
|View full text |Cite
|
Sign up to set email alerts
|

Product and Process Innovation as a Response to Increasing Imports and Foreign Direct Investment

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.The paper analyses the hypotheses that imports and inward foreign direct investment (FDI) have positive effects on the innovative activity of domestic firms because competition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
135
4
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 24 publications
14
135
4
3
Order By: Relevance
“…Several studies of firms in the manufacturing and service sectors in various countries have found that FDI and foreign ownership positively affected innovative activity and productivity. Firms operating locally with foreign investors have more researchers and learn more from more sources such as suppliers and customers, universities and their intra-firm global information (Love, Ashcroft, and Dunlop, 1996;Erdilek, 2005;Wagner, 2006;Blind and Jungmittag, 2004;Bertschek, 1995;Lofts and Loundes, 2000;Masso, Roolaht, and Varblane, 2010;Griffith, Redding, and van Reenen, 2004;Criscuolo, Haskel, and Slaughter, 2005). Other studies have shown that FDI may have no effect on innovation (Lööf, Ebersberger, and Jahansson, 2006;Balcet and Evangelista, 2005;Bertrand and Zuñiga, 2006;Almeida and Fernandes, 2006;Falk and Falk, 2006;Bishop and Wiseman, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies of firms in the manufacturing and service sectors in various countries have found that FDI and foreign ownership positively affected innovative activity and productivity. Firms operating locally with foreign investors have more researchers and learn more from more sources such as suppliers and customers, universities and their intra-firm global information (Love, Ashcroft, and Dunlop, 1996;Erdilek, 2005;Wagner, 2006;Blind and Jungmittag, 2004;Bertschek, 1995;Lofts and Loundes, 2000;Masso, Roolaht, and Varblane, 2010;Griffith, Redding, and van Reenen, 2004;Criscuolo, Haskel, and Slaughter, 2005). Other studies have shown that FDI may have no effect on innovation (Lööf, Ebersberger, and Jahansson, 2006;Balcet and Evangelista, 2005;Bertrand and Zuñiga, 2006;Almeida and Fernandes, 2006;Falk and Falk, 2006;Bishop and Wiseman, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An empirical example for our discussion of panel probit models is the analysis of rms' innovative activity as a response to imports and foreign direct investment (FDI) as considered in Bertschek (1995). The main hypothesis put forward in that paper is that imports and inward FDI have positive e ects on the innovative activity of domestic rms.…”
Section: Empirical Example Notation and Basic Assumptionsmentioning
confidence: 99%
“…However, the majority of these papers refer to the experience of developed countries. An interesting research of a country was done by Bertschek (1995). This author, with data of German companies, found that both FDI and imports have positive effects on the innovative activity of the national productive sector.…”
Section: Literature Reviewmentioning
confidence: 99%